2016
DOI: 10.1177/1420326x16670227
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and knowledge challenges in realizing smart homes: The case of small installer businesses

Abstract: Despite technological advances, smart home concepts are not receiving widespread adoption. Small businesses that install and maintain heating, security and energy-saving systems could play a major role in bringing advanced technologies to home owners. However, the role of such small installer businesses in the smart living industry is generally overlooked in practice as well as academic literature. This paper studies challenges small installer businesses face when offering smart home and smart living services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Another significant association was identified between the comfort service and barriers of lack of knowledge and psychological resistance, with an adjusted residual value of 2.30 (p-value < 0.05). The association between comfort services and the barrier of lack of knowledge and technological resistance may be explained by users' lack of knowledge about smart home functions (Keijzer-Broers and de Reuver, 2018). This lack of knowledge may even prevent the implementation of smart homes (Balta-Ozkan et al, 2013a), as evidenced by an empirical study that indicated the need to increase users' knowledge about smart home systems before their implementation (Meeks et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Another significant association was identified between the comfort service and barriers of lack of knowledge and psychological resistance, with an adjusted residual value of 2.30 (p-value < 0.05). The association between comfort services and the barrier of lack of knowledge and technological resistance may be explained by users' lack of knowledge about smart home functions (Keijzer-Broers and de Reuver, 2018). This lack of knowledge may even prevent the implementation of smart homes (Balta-Ozkan et al, 2013a), as evidenced by an empirical study that indicated the need to increase users' knowledge about smart home systems before their implementation (Meeks et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Even companies already providing technology products for health and care may find it difficult to take new emerging technologies as part of their business. Especially small technology companies may have challenges such as lack of knowledge and entrepreneurial skills, limited sharing of knowledge and lack of cooperation, similarly to small heating and security home system installer companies that consider taking part in the smart home and smart living business (Keijzer-Broers & de Reuver, 2018).…”
Section: Introductionmentioning
confidence: 99%